Mental Models, Magical Thinking, and Individual Differences - Turner, Phil; Sobolewska, Emilia (Human Technology, 2009)
Broadly, there are two mutually exclusive accounts of how people (non-specialist users) reason about and conceptualize interactive technology. The first is based on classical cognitive psychology and is characterized by the term mental model. The second, drawing on concepts from social cognition, observes that people often anthropomorphize technology. We argue that people are able to exhibit both of these quite different styles of cognition, which Baron-Cohen has described as systemizing and empathizing. The former is associated with the drive to analyze, explore, and construct a system, whereas the latter is the ability to spontaneously tune into another's thoughts and feelings. The propensity to systemize might give rise to a mental model, while the empathizing tendency might tend to anthropomorphize technology. We present an empirical study that lends support for the above position.